Study on the methanolic extracts of emilia sonchifolia and vernonia arborea (Compositae) - Hanafi, bin Mohammad. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Studies on the methanolic extracts have been carried out on the sample of Emilia sonchifolia, and Vernonia arborea. The methanol crude extracts were subjected to thin layer chromatography, 2-dimensional thin layer chromatography, column chromatography, and preparative thin layer chromatography for the isolation and purification analysis. For extraction four major spots in the crude extract Emilia sonchifolia and three major spots in the crude extract Vernonia arborea were observed. Crude extract Emilia sonchifolia indicated flavonoids due to appearance of yellow fluorescence color at Rf 0.42, 0.75, 0.90, and 0.94 in 2-dimensional thin layer chromatography. Fractions from methanol crude extracts of Emilia sonchifolia shows appearance of carbonyl compounds based on absorption at 1737.7 cm-I. From the toxicity test, crude extract Emilia sonchifolia showed toxicity result on brine shrimp (Artemia salina) with the LD50 value is 53.3.